Oregano powder substitution and shelf life in pork chorizo using Mexican oregano essential oil - Perales Jasso, Yessica J.; Gamez Noyola, Stephannie A.; Aranda Ruiz, Juana; Hernández Martínez, Carlos Alberto; Gutiérrez Soto, Juanita Guadalupe; Luna Maldonado, Alejandro I.; Silva Vázquez, Ramón; Hume, Michael E.; Méndez Zamora, Gerardo (2018)
Abstract The aim of this study was to evaluate the effect of oregano essential oil (MOO) from Mexican oregano, Lippia berlandieri Schauer, as substitute for Mexican oregano powder (MOP) on pork chorizo physicochemical characteristics, texture, antioxidant capacity, aerobic bacteria colony counts, and sensory evaluation under storage conditions over 7 d. The treatments were T1 = chorizo + 0.1% MOP and T2 = chorizo + 0.1% MOO. The pH, redness (a*), yellowness (b*), Chroma, and browning index (BI) were affected by treatments and storage time. T2 presented lower pH (5.27) at d 1 than at d 7 (5.34), as well as a* (23.13 vs. 25.27), b* (14.85 vs. 17.45), Chroma (28.60 vs. 30.79), and BI (103.42 vs. 109.82) were higher at d 7. At d 1, hardness (1392.75 vs. 872.29 g), springiness (0.3675 vs. 0.3351 mm), gumminess (491.45 vs. 284.38 g), and chewiness (180.25 vs. 95.43 g mm) were higher in T1 than T2. Aerobic bacteria counts (T1—4.19 vs. 4.73 log CFU/g and T2—4.37 vs. 4.50 log CFU/g, respectively) increased within each treatment at d 7. Antioxidant capacity was not affected (26.48 and 27.42%). Oregano odor was different at 7 d with T2 having a stronger odor (5.70) than T1 with oregano powder (4.63). Mexican oregano essential oil in the pork chorizo formulation improved pH, color parameters, textural profile, and sensory characteristics.